Upregulation of Translationally Controlled Tumor Protein Is Associated With Cervical Cancer Progression - Zhu, Xiaoyu; Ren, Ji; Xu, Dianqin; Cheng, Di; Wang, Wei; Ren, Jie; Xiao, Ziwen; Jiang, Hongmei; Ding, Yan; Tan, Yujie (Frontiers in Molecular Biosciences, 2021)
Outside a few affluent countries with adequate vaccination and screening coverage, cervical cancer remains the leading detriment for women in many countries. Currently, a major problem is that substantial proportion of patients are already at an advanced cancer stage when diagnosed. There is increasing evidence that indicates the involvement of Translationally Controlled Tumour Protein (TPT1) overexpression in cancer development, but little is known about its implication in cervical cancer. We assessed the levels of TPT1 in surgical tissue and sera of patients with cervicitis, Cervical Intraepithelial Neoplasia III and cervical cancer, as well as in normal and cancerous cervical cell lines. Gene sets, pathways and functional protein interactions associated with TPT1 were identified using TCGA data cohort of cervical cancer. We found that the TPT1 expression was significantly increased in cervical cancer tissue compared to all non-malignant cervical tissues, including samples of cervicitis, Cervical Intraepithelial Neoplasia III and normal controls. Serum level of TPT1 was also increased in cervical cancer patients compared to healthy subjects. Furthermore, elevated TPT1 expression was significantly correlated with lymph node metastasis and a low differentiation degree of the cancer. In the cancerous tissues and cell lines, selective markers of PI3K/AKT/mTOR pathway over-activation, apoptosis repression and EMT were detected, and their interaction with TPT1 was supported by biometrics analyses. Our results, for the first time, demonstrate a strong correlation of up-regulated TPT1 expression to cervical cancer progression, suggesting a potential biomarker for diagnosis of cervical cancer.